Structure, function, and pathology of PHF23 - Liu, Linlin; Zhang, Rui; Liu, Rui; Liu, Yu; Ren, Yanming (Frontiers in Cell and Developmental Biology, 2025)
Plant Homeodomain Finger Protein 23 (PHF23) is a member of the Plant Homeodomain (PHD) finger protein family and has been extensively reported since its discovery. Numerous studies have demonstrated that PHF23 plays a crucial role in various biological processes, such as gene expression regulation, autophagy, and tumorigenesis. Additionally, PHF23 is associated with various diseases including various malignancies, osteoarthritis, and tuberculosis, all of which currently lack effective and targeted treatment options. Therefore, this review systematically summarizes the existing literature on PHF23, and provides a comprehensive overview of the structure and function of PHF23, and focuses on its relationship with multiple diseases. We aim to advance PHF23 research to establish it as a novel therapeutic and diagnostic target, offering new hope for patients with related diseases while reducing adverse clinical outcomes.